Pengaruh Kecerdasan Emosional, Kompetensi Dan Kecerdasan Spiritual Terhadap Kinerja Aparatur Sipil Negara Kantor Kementerian Agama Kabupaten Mamasa - Hasanudin; Milka Pasulu; Ferdinand Poylema (Jurnal Online Manajemen ELPEI, 2023)
This study aims 1) to find out and prove the effect of emotional intelligence on the performance of state civil servants at the Office of the Ministry of Religion in Kab. Mamasa, 2) to find out and prove the effect of competence on the performance of the State Civil Apparatus at the Office of the Ministry of Religion of the Regency. Mamasa, 3) to find out and prove the influence of spiritual intelligence on the performance of the State Civil Apparatus at the Office of the Ministry of Religion in Kab. Mamasa, 4) ) to find out and prove the influence of emotional intelligence, competence and spiritual intelligence on the performance of the State Civil Apparatus at the Office of the Ministry of Religion of Mamasa Regency. Data collection is done through documentation, observation, and questionnaires. The ASN sample consisted of 66 respondents. Data processing consists of descriptive analysis, correlation analysis and regression analysis The results showed that with a significant level of 5% and degrees of freedom df1 = 3 and df2 = 65, the f table was obtained (3:65) = 2.75. Based on the ANOVA test or the F test from the SPSS output, it can be seen that the f count is 19,135 > 2.75 the f table value and the probability is 0.000 <0.05. More precisely, the calculated F value is compared to the F table where if F count > F table then simultaneously emotional intelligence, competence and spiritual intelligence on the performance of the State Civil Apparatus at the Office of the Ministry of Religion of Mamasa Regency. This means that the hypothesis of the two researchers is accepted.